DISIPLIN SANTRI BELAJAR DI ASRAMA PADA PONDOK PESANTREN DAR EL HIKMAH KELURAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU PROVINSI RIAU - Ilmiyani, Nur; Maemunaty, Titi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: this study aims to determine the discipline of students studying in a dormitory at the Dar El Hikmah islamic boarding school in the simpang baru sub-district of the Tampan Pekanbaru District Riau Province. The formulation of the problem in this study is how high is the discipline of students studying in boarding school in the Dar El Hikmah islamic boarding school in the in the simpang baru sub-district of the Tampan pekanbaru District Riau Province. This research is descriptoive with a quantitative approach that aims to describe the results of reseach with number?s. Sampling technique using simple random sampling technique. Data collection techniques in this study were 92 questionnaire items. Data obtained from respondents totaling 30 people for trian sample and 92 people for the study sample. The result of data analysis showed that the discipline of students studying in boarding school in the Dar El Hikmah islamic boarding school in the in the Simpang Baru Sub-District Of The Tampan Pekanbaru District Riau Province was relatively high. Key Words: Santri Learning Discipline